2019
DOI: 10.1177/1744806919827469
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of hypersensitivity in chronic inflammatory pain by the de novo DNA methyltransferase Dnmt3a2

Abstract: Chronic pain is a pathological manifestation of neuronal plasticity supported by altered gene transcription in spinal cord neurons that results in long-lasting hypersensitivity. Recently, the concept that epigenetic regulators might be important in pathological pain has emerged, but a clear understanding of the molecular players involved in the process is still lacking. In this study, we linked Dnmt3a2, a synaptic activity-regulated de novo DNA methyltransferase, to chronic inflammatory pain. We observed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…Taken together, these studies indicated that particularly the function of Dnmt3a is important for hippocampal memory formation. We showed that the Dnmt3a isoform, Dnmt3a2 is required for different forms of long-lasting neuronal adaptions, including long-term memory formation, and that the expression of Dnmt3a2, but not Dnmt3a1, is induced by neuronal activity and learning [12][13][14][15] . Therefore in the current study, we employed activity-dependent tools to overexpress and reinforce the function of the activity- Our results demonstrate that restricting the overexpression of Dnmt3a2 to the majority of the DG neuronal population (~75%) activated by CFC was sufficient to positively modulate the memory engram, and to specifically strengthen the memory encoding for the aversive context.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Taken together, these studies indicated that particularly the function of Dnmt3a is important for hippocampal memory formation. We showed that the Dnmt3a isoform, Dnmt3a2 is required for different forms of long-lasting neuronal adaptions, including long-term memory formation, and that the expression of Dnmt3a2, but not Dnmt3a1, is induced by neuronal activity and learning [12][13][14][15] . Therefore in the current study, we employed activity-dependent tools to overexpress and reinforce the function of the activity- Our results demonstrate that restricting the overexpression of Dnmt3a2 to the majority of the DG neuronal population (~75%) activated by CFC was sufficient to positively modulate the memory engram, and to specifically strengthen the memory encoding for the aversive context.…”
Section: Discussionmentioning
confidence: 97%
“…Recently developed technologies 10,11 allowed us to manipulate the levels of a DNA methyltransferase (Dnmt) specifically within hippocampal neuronal ensembles formed after contextual fear learning and to investigate the consequences of this manipulation for the strength of fear memory and stability of the engram. In particular, we elevated the levels of the de novo DNA methyltransferase (Dnmt3a2) in the dentate gyrus (DG) of the mouse hippocampus, as Dnmt3a2 expression is regulated by neuronal activity 12 and has established functions in long-lasting neuronal adaptations [13][14][15] . We showed that reinforcing DNA methylation-related mechanisms through Dnmt3a2 overexpression within memory-encoding neuronal ensembles specifically during consolidation was sufficient to strengthen contextual fear memory and the stability of the engram.…”
mentioning
confidence: 99%
“…However, the studies agree that no alterations of DNMT3a expression exist at day 3 following CFA injection (Li et al, 2018;Qi et al, 2012). Another study by Oliveira et al (2019) found a significantly increased expression of DNMT3a2 in mouse DRG 6 hr after CFA injection with no detectable increase at day 1 or day 2 following the injection (Oliveira et al, 2019).…”
Section: Inflammatory Pain Modelsmentioning
confidence: 67%
“…Chronic pain affects a great proportion of the population worldwide (Massart et al., 2016; Oliveira et al., 2019), posing major health problems affecting the quality of life of the individual (Denk & Mcmahon, 2012; Descalzi et al., 2015; Shao et al., 2017) and leading to significant socioeconomic costs (Denk & Mcmahon, 2012; Descalzi et al., 2015; Shao et al., 2017). The current, revised International Association for the Study of Pain (IASP) definition of pain is as follows: “An unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage” (Raja et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The method used to construct, package, and purify rAAVs has been previously described. 89,90 rAAV serotypes 1/2 were produced by cotransfection of HEK293 cells by standard calcium phosphate precipitation. Before transfection, culture medium was replaced with fresh modified Dulbecco's medium (Iscove's modified Dulbecco's medium; Life Technologies, Carlsbad, CA, USA) containing 5% FBS without antibiotics.…”
Section: Raavsmentioning
confidence: 99%